Gallstone Disease Does Not Predict Liver Histology in Nonalcoholic Fatty Liver Disease - YILMAZ, YUSUF (EDITORIAL OFFICE GUT & LIVER, 2014)
Background/Aims: We sought to examine whether the presence of gallstone disease (GD) in patients with biopsy-proven nonalcoholic fatty liver disease (NAFLD) is associated with liver fibrosis and histological nonalcoholic steatohepatitis (NASH) score. Methods: We included 441 Turkish patients with biopsy-proven NAFLD. GD was diagnosed in the presence of sonographic evidence of gallstones, echogenic material within the gallbladder with constant shadowing and little or no visualization of the gallbladder or absence of gallbladder at ultrasonography, coupled with a history of cholecystectomy. Results: Fifty-four patients (12.2%) had GD (GD+ subjects). Compared with the GD- subjects, GD+ patients were older, had a higher body mass index and were more likely to be female and have metabolic syndrome. However, GD+ patients did not have a higher risk of advanced fibrosis or definite NASH on histology. After adjustment for potential confounding variables, the prevalence of GD in NAFLD patients was not associated with significant fibrosis (>= 2) (odds ratio [OR], 1.06; 95% confidence interval [Cl], 0.53 to 2.21; p=0.68) or definite NASH (OR, 1.03; 95% Cl, 0.495 to 2.12; p=0.84). Conclusions: The presence of GD is not independently associated with advanced fibrosis and definite NASH in adult Turkish patients with biopsy-proven NAFLD.
Keywords: Gallstone disease; Non-alcoholic fatty liver disease; Nonalcoholic steatohepatitis; Fibrosis; METABOLIC SYNDROME; GALLBLADDER-DISEASE; INSULIN-RESISTANCE; RISK-FACTORS; STEATOHEPATITIS; PROGRESSION; PREVALENCE